Zurbarán's Cartellini: Presence and the Paragone. Issue 1 (2nd January 2017) - Ostrow, Steven F.
Abstract : The cartellino—a small trompe l'oeil slip of paper bearing the artist's signature—is examined in early modern Spanish painting, focusing on the works of Francisco de Zurbarán and the ways he exploited the device metapictorially. In his hands, it inserted his presence in works from his brush and commented on the art of painting, articulating his position on the paragone, the much-debated comparison between painting and sculpture, which he demonstrated most vividly in his images of the Holy Face, works in which Veronica's veil, a variation of the cartellino, is presented for our meditation.